PERBANDINGAN KADAR LOW DENSITY LIPOPROTEIN CHOLESTEROL( LDL-C) PADA PEROKOK DAN BUKAN PEROKOK - Kaparang, Patrix; Wangko, Sunny; Kaseke, Marie (e-Biomedik, 2013)
Abstract: Smoking in many forms is the main risks factor of atherosclerotic process and coronay heart diseases. Cigarette smoking results in increases of total cholesterol, triglyserida, LDL-C, and VLDL-C, and a decrease of HDL-C blood levels. The aim of this study was to compare the LDL-C levels of smokers with non-smokers males. This was an observational study with a cross sectional design. This study was done in the Faculty of Medicine, University of Sam Ratulangi Manado from November to Desember 2012, by using a purposive sampling technique. There were 60 smoker students and non-smoker students of semester 7 Faculty of Medicine, University of Sam Ratulangi, Manado who fulfilled the inclulsion criteria. Data were taken from questionnaires and examinations of LDL-C levels. LDL-C levels were analyzed by using the SPSS version 20. The results showed that the analysis of the comparison of LDL-C levels of the smoker students’ with of the non-smokers’students had a P-value 0.911. Conclusion: There was no significant difference of the LDL-C levels between smokers and non-smokers. Keywords: atherosclerotic, LDL-C level, smoker, non-smoker Abstrak: Merokok dalam berbagai bentuk merupakan faktor risiko utama aterosklerosis dan penyakit jantung koroner. Rokok menyebabkan peningkatan konsentrasi serum kolesterol total, trigliserida, LDL-C, VLDL-C dan penurunan HDL-C. LDL-C yang berlebihan dalam plasma menginduksi terjadinya aterosklerosis.Penelitian ini bertujuan untuk membandingkan kadar LDL-C pada laki-laki perokok dengan yang bukan perokok. Penelitian ini bersifat observasional dengan desain penelitian potong lintang. Penelitian dilakukan di Fakultas Kedokteran Universitas Sam Ratulangi Manado pada bulan November-Desember 2012. Teknik pengambilan sampel menggunakan purposive sampling. Sampel diperoleh sebanyak 60 orang mahasiswa kaki-laki semester 7 Fakultas Kedokteran Unsrat tahun ajaran 2012 yang perokok dan bukan perokok, yang memenuhi criteria inklusi. Data didapatkan dari kuesioner dan pemeriksaan kadar LDL-C serum. Kadar LDL-C dianalisis dengan menggunakan SPSS versi 20. Hasil analisis perbandingan kadar LDL-C antara mahasiswa perokok dan bukan perokok menunjukkan nilai P = 0,911. Simpulan: Tidak terdapat perbedaan bermakna antara kadar LDL-C antara perokok dan bukan perokok. Kata kunci: aterosklerosis,kadar LDL-C, perokok.